2023
DOI: 10.1017/flo.2022.30
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic semen analysis for veterinary male bovine infertility assessment

Abstract: We demonstrate through the use of a unique acoustically driven microfluidic extensional rheometry platform (ADMiER) that a single measurement – i.e. the time required for a liquid bridge filament comprising a microlitre semen sample to thin and break up under elastocapillary stresses – constitutes an appropriate proxy for quantifying the motile sperm concentration of the sample in place of computer-assisted sperm analysis (CASA) and haemocytometer measurements used in conventional semen assessment – without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…They showed that microstructures with smaller curves are able to concentrate sperms by an order of magnitude. 43 Apart from biologically-inspired mechanisms mentioned above, there have been some attempts to employ external non-natural forces such as electrophoresis, 44 dielectrophoresis, 45 impedance cytometry, 46,47 and acoustics, 48 for sperm sorting and screening. In one such attempt, surface acoustic waves were utilized to create virtual passageways, guiding viable and motile sperms across the microfluidic channel to the collection outlet.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that microstructures with smaller curves are able to concentrate sperms by an order of magnitude. 43 Apart from biologically-inspired mechanisms mentioned above, there have been some attempts to employ external non-natural forces such as electrophoresis, 44 dielectrophoresis, 45 impedance cytometry, 46,47 and acoustics, 48 for sperm sorting and screening. In one such attempt, surface acoustic waves were utilized to create virtual passageways, guiding viable and motile sperms across the microfluidic channel to the collection outlet.…”
Section: Introductionmentioning
confidence: 99%